Diroximel fumarate (DRF) in patients with relapsing–remitting multiple sclerosis: Interim safety and efficacy results from the phase 3 EVOLVE-MS-1 study. (November 2020) - Naismith, Robert T; Wolinsky, Jerry S; Wundes, Annette; LaGanke, Christopher; Arnold, Douglas L; Obradovic, Dragana; Freedman, Mark S; Gudesblatt, Mark; Ziemssen, Tjalf; Kandinov, Boris; Bidollari, Ilda; Lopez-Bresnahan, Maria; et al.
Background: Diroximel fumarate (DRF) is a novel oral fumarate for patients with relapsing–remitting multiple sclerosis (RRMS). DRF and the approved drug dimethyl fumarate yield bioequivalent exposure to the active metabolite monomethyl fumarate; thus, efficacy/safety profiles are expected to be similar. However, DRF's distinct chemical structure may result in a differentiated gastrointestinal (GI) tolerability profile. Objective: To report interim safety/efficacy findings from patients in the ongoing EVOLVE-MS-1 study. Methods: EVOLVE-MS-1 is an ongoing, open-label, 96-week, phase 3 study assessing DRF safety, tolerability, and efficacy in RRMS patients. Primary endpoint is safety and tolerability; efficacy endpoints are exploratory. Results: As of March 2018, 696 patients were enrolled; median exposure was 59.9 (range: 0.1–98.9) weeks. Adverse events (AEs) occurred in 84.6% (589/696) of patients; the majority were mild (31.2%; 217/696) or moderate (46.8%; 326/696) in severity. Overall treatment discontinuation was 14.9%; 6.3% due to AEs and <1% due to GI AEs. At Week 48, mean number of gadolinium-enhancing lesions was significantly reduced from baseline (77%; p < 0.0001) and adjusted annualized relapse rate was low (0.16; 95% confidence interval: 0.13–0.20). Conclusion: Interim data from EVOLVE-MS-1 suggest DRF is a well-tolerated treatment with a favorable safety/efficacy profile for patients with RRMS.